1976
DOI: 10.2172/7355628
|View full text |Cite
|
Sign up to set email alerts
|

Vapor--liquid--solid phase equilibria of radioactive sodium salt wastes at Hanford

Abstract: This system simuZates radioactive sodium saZt wastes stored in underground tanks at Sanford. Equitibrium water vapor pressure of the aqueous phase and solub€Zity of the saZts were measured. as a function of temperaturo and NaOH concentration.These data are used to predict deZiquescence of stored saZt.wastes and also to predict the chemicaZ / identity of soZid residues from evaporation of Ziquid wastes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(78 citation statements)
references
References 1 publication
5
73
0
Order By: Relevance
“…1,2 Processes designed to minimize the volume of high-level waste through conversion to glassy phases require transporting waste solutions near-saturated with aluminum-containing species from holding tank to processing center. The uncontrolled precipitation within transfer lines results in clogged pipes and lines and fouled ion exchangers, with the potential to shut down processing operations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Processes designed to minimize the volume of high-level waste through conversion to glassy phases require transporting waste solutions near-saturated with aluminum-containing species from holding tank to processing center. The uncontrolled precipitation within transfer lines results in clogged pipes and lines and fouled ion exchangers, with the potential to shut down processing operations.…”
Section: Discussionmentioning
confidence: 99%
“…The uncontrolled precipitation within transfer lines results in clogged pipes and lines and fouled ion exchangers, with the potential to shut down processing operations. 2 The principal focus of our research was to maintain the fluidity of aluminum-or silicon-containing suspensions and solutions during transport, whether by preventing particle formation, stabilizing colloidal particles in suspension, or by combining partial dissolution with particle stabilization. We have found that all of these can be effected in aluminum-containing solutions using the simple organic, citric acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The substantial water content found in Bryan's dried simulant illustrates how strongly this simulant retains water and suggests that actual lOlSY waste should be slow to dry during the VDTT removal operation; wastes containing substantial amounts of sodium hydroxide can retain substantial amounts of water (Scheele, Bredt, and Sell 1996;Barney 1976;Fauske et al 1995).…”
Section: 4mentioning
confidence: 99%
“…Figure 1 (Barney 1976) is shows solubilities of aluminum species versus sodium hydroxide. The curves with the dotted lines are from literature for the Na,O -A1203-H20 system.…”
Section: (4)mentioning
confidence: 99%